2011
DOI: 10.1118/1.3635222
|View full text |Cite
|
Sign up to set email alerts
|

In-patient to isocenter KERMA ratios in CT

Abstract: Purpose: To estimate in-patient KERMA for specific organs in computed tomography (CT) scanning using ratios to isocenter free-in-air KERMA obtained using a Rando phantom. Method: A CT scan of an anthropomorphic phantom results in an air KERMA K at a selected phantom location and air kerma K CT at the CT scanner isocenter when the scan is repeated in the absence of the phantom. The authors define the KERMA ratio (R K ) as K= K CT , which were experimentally determined in a Male Rando Phantom using lithium fluor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Table 2 provides a summary of the radiographic techniques used to perform scans on each of the four pediatric phantoms. For these scanners, it is possible to obtain nominal values of K CT , which is numerically equal to CTDI air divided by the over-beaming factor for that scanner/scan geometry combination [6], and to estimate the radiation dose in a 16-cm diameter acrylic phantom that approximates a pediatric patient [14]. Based on the radiographic techniques, values of K CT used in this work were estimated using the ImPACT calculator to range from~40 mGy at 80 kV to 150 mGy at 140 kV in the GE scanner.…”
Section: Ct Scansmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 2 provides a summary of the radiographic techniques used to perform scans on each of the four pediatric phantoms. For these scanners, it is possible to obtain nominal values of K CT , which is numerically equal to CTDI air divided by the over-beaming factor for that scanner/scan geometry combination [6], and to estimate the radiation dose in a 16-cm diameter acrylic phantom that approximates a pediatric patient [14]. Based on the radiographic techniques, values of K CT used in this work were estimated using the ImPACT calculator to range from~40 mGy at 80 kV to 150 mGy at 140 kV in the GE scanner.…”
Section: Ct Scansmentioning
confidence: 99%
“…This method is conceptually simple and based on in-air measurements that can be readily obtained for any clinical CT scanner [6]. KERMA is an acronym for Kinetic Energy Released in Matter, and has the same units as dose (the Gray [Gy]), defined as one joule of energy deposited per kilogram of material.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Initial attempts to estimate the radiation dose a fetus would receive from a CT exam were based either on phantom measurements, Monte Carlo (MC) simulations of geometric phantoms, or a combination of the two. [4][5][6][7][8][9][10][11][12][13] The approach described by Felmlee et al 4 , for example, uses anthropomorphic phantom measurements and measured Computed Tomography Dose Index (CTDI) values. Some important limitations of these early efforts relate to their use of simplified, geometric models and assumptions of nonvarying maternal anatomy in a single-size patient model.…”
Section: Introductionmentioning
confidence: 99%
“…However, Huda et al reported conversion factors from _ K air to effective dose or organ dose 17. 2 They then calculated the effects of both primary and scattered photons separately at different positions in the phantom.…”
mentioning
confidence: 99%
“…9 One reason for this may be the energy depen- or organ dose. 17 At this point, the _ K 0Àw=oÀA and _ K 0ÀwÀA might be utilized as well, although no definite claim can be made without verification. On the other hand, the unit of K 0 is mGy/s, not mGy/rotation as for CTDI vol .…”
mentioning
confidence: 99%